Accuracy of acoustic evaluation of swallowing as a diagnostic method of dysphagia in individuals affected by stroke: preliminary analysis - Enz, Vivian (2022)
After a stroke, more than half of the patients have some kind of disability, and dysphagia is frequently found. Cervical auscultation by Doppler sonar is an innovative technique with gain of credibility in the clinical evaluation of swallowing. To verify the diagnostic accuracy of Doppler sonar along with the DeglutiSom® software as an auxiliary method in the evaluation of oropharyngeal dysphagia in patients after stroke. The research is a cross-sectional, uncontrolled, blind, quantitative study with systematic random sampling. Patients from inpatient and outpatient units of a reference hospital with a stroke care unit were concomitantly submitted to both Doppler sonar and Fiberoptic Endoscopic Evaluation of Swallowing (FEES®). Seventy-three audio files collected from 26 patients through Doppler sonar were analyzed using DeglutiSom® software and confronted with the FEES® report, regarding three food consistencies offered to them during the exam. The study showed that the Doppler sonar correctly identified, among all the analyzed files, those that actually presented tracheal aspiration as well as it effectively identified patients who did not aspirate. The Youden index of 0.91 corroborates this information, showing a promising accuracy in detecting tracheal aspiration in the studied sample. The study evaluates the diagnostic accuracy of Doppler sonar, showing that it can be used as a valuable tool in the diagnosis of tracheal aspiration in patients after stroke. It is important to emphasize that the identification of residue by this method requires further studies. Also, larger sample size and more than one blind evaluator should be considered in future researches to increase the reliability of the proposed method.